Low folate status and indoor pollution are risk factors for endemic optic neuropathy in Tanzania. Issue 10 (6th July 2011) - Hodson, Katherine E; Bowman, Richard J; Mafwiri, Milka; Wood, Mark; Mhoro, Vincent; Cox, Sharon E
Abstract : Aims: Bilateral optic neuropathy in Dar-es-Salaam, Tanzania was first reported as an epidemic in 1988. Now argued to be endemic in 2010, the aetiology remains unclear. The authors investigated the hypothesis that low folate and vitamin B12 status are associated with optic neuropathy, and also sought to investigate whether mercury, commonly used drugs, dietary factors and indoor pollution may also be risk factors. Methods: 57 cases and 102 controls were recruited from two tertiary referral centres in Dar-es-Salaam. Data were collected on demographic characteristics, diet, medication history and HIV status. Folate and vitamin B12 (holo-transcobalamin) were measured in stored serum samples. Exposure to mercury was assessed from concentrations in random urine samples. Results: Cooking indoors more than twice per week (OR 54.48 (95% CI 9.30 to 319.10)) and indoor use of charcoal or firewood (OR 21.20 (95% CI 2.51 to 179.36)) increased the risk of optic neuropathy. Risk was reduced in those with a higher folate status (highest versus lowest quartile OR=0.11 (95% CI 0.02 to 0.51)) and higher protein intakes (OR=0.84 (95% CI 0.72 to 0.96). No association was found with mercury exposure or any common drug or food commodity. Conclusion: This study presents the first direct evidence of low folate status and indoor pollution in the aetiology of endemic bilateral optic neuropathy in Tanzania.